P129 Prefrontal cortical excitability enhancement after cathodal tDCS: A multimodal study. Issue 3 (March 2017) - Rodella, C.; Cespon, J.; Miniussi, C.; Rossini, P.M.; Pellicciari, M.C.
Abstract : Introduction: Transcranial direct current stimulation (tDCS) is a non-invasive technique that is increasingly used in neuroscience, as it has the potential to induce cortical excitability changes (Nitsche et al., 2008; Woods et al., 2016). Specifically, tDCS has been widely applied to study cognition. Nevertheless, differently from motor system, applying tDCS in cognitive domains does not allow to have a direct physiological measure able to monitor polarity-dependent effects on cortical excitability. Event related potentials (ERPs) and TMS-evoked potentials (TEPs) could represent valuable surrogate markers of cortical excitability changes (Kesser et al., 2011; Miniussi and Thut, 2010). Objective: The purpose of the present study was verifying the capability of tDCS to modulate cortical reactivity (using TEPs) of prefrontal cortex and characterizing the electrophysiological correlates (using ERPs) of cognitive processes underlying a working memory task. Materials & methods: A sample of healthy young participants performed a 3-back task while EEG was recording before and after applying 13 min of tDCS (anodal, cathodal and sham sessions) over the left dorsolateral prefrontal cortex (DLPFC). TEPs were also collected before and after the tDCS. Results: Results showed no tDCS polarity-dependent differences in task performance. However, increased prefrontal activity was observed at 150–200 ms over the stimulated region after cathodal tDCS. Furthermore, parietal activity underlying P3 component, which was typically related to working memory processes (Kesser et al., 2011), was larger after cathodal tDCS. Surprisingly, differences were found only after cathodal tDCS. These results were consistent with TEPs, which were modulated by tDCS in a polarity-dependent manner. Conclusion: Our findings demonstrate that tDCS is able to induce prefrontal cortical activity and reactivity changes, which can be assessed by EEG and TMS-EEG measures, even when behavioral data are not sensitive enough to reveal functional modifications. Overall, these results suggest potential clinical application of tDCS and utility of ERPs and TEPs to monitor cortical excitability modifications induced by the stimulation protocols.